Efecto del extracto hidroalcohólico de las flores de cantua buxifolia juss. ex lam. “flor sagrada de los incas” sobre el crecimiento de staphylococcus aureus, escherichia coli y pseudomonas aeruginosa, in vitro. - Serrano Bringas, Alejandra Marión (2012)
In the present work were identified the fitoconstituyentes of the hydroalcoholic extract of flowers of Cantua buxifolia Juss. ex Lam. “Flor Sagrada de los Incas”. The phytoconstituents found were catechins, reducing sugars, coumarins, triterpenes, steroids, saponins, tannins, amino acids, quinones, cardenolides, flavonoids and anthocyanins. Likewise, the effect of the hydroalcoholic extract of flowers of Cantua buxifolia over the growth of Staphylococcus aureus, Escherichia coli and Pseudomonas aeruginosa, in vitro. were evaluated using three different concentrations (0,5 mg; 1,0 mg and 1,5 mg/mL) of hydroalcoholic extract of flowers of Cantua buxifolia. To determinated the effect of the hydroalcoholic extract was used the method of diffusion in agar, being planted in Mueller Hinton agar plates with each of the microorganisms, later there were done 5 perforations of 11 mm of diameter containing 200 uL of gentamicina (10 mg/mL), 200 uL of dimetilsulfóxido and 200 uL of every concentration of extract and incubated to 37°C, for a period of 24 h. Three tests were realized by every bacterium. The results were expressed as diameter (mm) of the halo of inhibition of growth of P. aeruginosa, E. coli and S. aureus respectively. It was found that the extract hidroalcohólico of the flowers of Cantua buxifolia inhibit the growth of P. aeruginosa, E. coli and S. aureus, in vitro. And as the concentrations of the extract increase in the range of 0,5 mg/mL to 1,5 mg/mL increases too the diameter of the halo of inhibition of the growth of P. aeruginosa, E. coli and S. aureus. in vitro.